Epidermal micromorphological futures in taxonomy of Bromus wolgensis Fisch. ex J. Jacq. f. (Poaceae) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Ultrastructure of leaf surfaces of Bromus squarrosus L. and B. wolgensis Fisch. ex J. Jacq. f. was examined by SEM. It is shown that their epiderma consists of long, crown, silica cells and stomatal cells. Morphological characters and patterns of these cells are very similar in both taxa. In result, recognition of both species is not supported by the studied micromorphological features.
Keywords: Bromus, epidermis, micromorphology, ultrastructure, SEM, taxonomy.